463 A research on e-devices and walking among teens in Shanghai: how they do and what they say. (1st September 2016) - Wang, Fannie; Yu, Yan; Wang, Mulder; Hou, Xinyi; Cui, Monica; Peng, Juanjuan; Jiang, Wenjuan
Abstract : Background: Road traffic accidents is the first killer to teens aged 15–17 worldwide. In China, the same trend happens on teens. They are the group walking independently on the one hand, they are the group with the highest increasing rate on web-surfacing through mobile phone on the other hand. This research presented the results through observation, group discussion and questionnaire on teens distracted walking by e-devices in Shanghai, which is the first of its kind in China. Methods: 8250 observations of teens in 8 communities in fall 2014 and spring 2015 were recorded. Observers conducted two morning and afternoon sessions at cross roads, on different days but at the same time, on regular school days in good weather. Each observer focused on one crossing location. 8 focus group discussions were conducted among 176 teens and 1000 questionnaires were completed by teens in 8 communities. Results: 50% of teens reported use of e-devices while walking in the questionnaire. Reported by observers at cross roads, 240 out of 8250 teens were observed distraction by e-devices while crossing in a quick traffic flow with a car passing by every 2.7 seconds. The distraction rate in the afternoon is 1.9 times vs morning. The most frequent forms of distraction were headphones 42.5%, texting 22.5%, game 15.8%, and talking on the phones (10.4%). During focus groups, 86.6% of teens perceived either senior or junior groups at greater risk. Safety talks on walking with e-devices with parents is in need among teens. Conclusions: Teens represent a growing proportion of road traffic victims. Prevalance use of e-devices among teens proposed growing risk. Evidence-based intervention is strenuous in need.